Elementary nervous systems - Arendt, Detlev (Philosophical transactions. Series B, Biological sciences, 2021)
The evolutionary origin of the nervous system has been a matter of long-standing debate. This is due to the different perspectives taken. Earlier studies addressed nervous system origins at the cellular level. They focused on the selective advantage of the first neuron in its local context, and considered vertical sensory-motor reflex arcs the first nervous system. Later studies emphasized the value of the nervous system at the tissue level. Rather than acting locally, early neurons were seen as part of an elementary nerve net that enabled the horizontal coordination of tissue movements. Opinions have also differed on the nature of effector cells. While most authors have favoured contractile systems, others see the key output of the incipient nervous system in the coordination of motile cilia, or the secretion of antimicrobial peptides. I will discuss these divergent views and explore how they can be validated by molecular and single-cell data. From this survey, possible consensus emerges: (i) the first manifestation of the nervous system likely was a nerve net, whereas specialized local circuits evolved later; (ii) different nerve nets may have evolved for the coordination of contractile or cilia-driven movements; (iii) all evolving nerve nets facilitated new forms of animal behaviour with increasing body size. - - This article is part of the theme issue ‘Basal cognition: multicellularity, neurons and the cognitive lens’.